DETERMINAÇÃO EXPERIMENTAL DA DENSIDADE VOLUMÉTRICA MÉDIA DE ENERGIA EM PINOS ENDODÔNTICOS TRANSLÚCIDOS - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2016)
The use of fiber posts in endodontic teeth restorations has been very frequent. These posts have conical shape and it is usually formed by glass fibers packaged in epoxy resin. Microscopy studies were conducted to investigate the structure of four models of fiberglass posts manufactured by FGM (DC 0.5, DC1, DC2 and DC3 models), and it was possible to verify inhomogeneities. The models of posts used in this study are translucent and, in clinical use, it is cemented into the tooth with light curing activated resin. During the clinical procedure of cementing a post in the tooth, light from a curing light impinge at the base of the post transmitting light to its interior. Part of this light is spread out by the side surface of the post. This study proposes a new methodology in order to investigate the spreading of light by endodontic posts in the orthogonal direction to its axis. This methodology fills out an dentist demand, e by means of it, it is possible to obtain light intensity profiles spread out along the length of a post. Comparing to previously published methods, this one uses the phase sensitive detection and the possibility to control the optical aperture in the experiment. The resulting profiles show a like exponential decay of light along the post, which allow us to obtain an linear attenuation coefficient for the different posts models studied. From the experimental results it is shown a way to calculate the light density of volumetric energy inside the post. The advantages of this new method are: (a) the results lead to much better characterization of the samples with more measured points and (b) the small optical aperture that provides better resolution.
Keywords: pinos endodônticos; luz espalhada; densidade de energia; endodontic pins; spread light; energy density; CNPQ::CIENCIAS EXATAS E DA TERRA::FISICA